2021
DOI: 10.21203/rs.3.rs-942066/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of PTPLAD1 as a Novel Tumor Suppressor and its Implication in Metastatic Colon Cancer Therapy

Abstract: Background: Colon cancer is one of the most common malignant cancers, and cancer metastasis always leads to a failure of clinical treatment. Although there have been many studies on the process of colon cancer progression, the detailed mechanism of colon cancer metastasis still remains unclear, and more effective drugs targeting colon cancer metastasis are urgently needed. This study aims to explore novel effectors involved in colon cancer metastasis and screen out potential targeted drug for colon cancer ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Beta-Carotene is thought to modulate telomerase activity in old age [43]. Of note, we found that almost all these antiaging plant supplements increased the abundance of A. muciniphila to varying degrees [44][45][46][47]. However, it has not been possible to determine whether the anti-aging effects of these plant supplements are associated with an increased abundance of A. muciniphila.…”
Section: A Muciniphila and Agingmentioning
confidence: 80%
“…Beta-Carotene is thought to modulate telomerase activity in old age [43]. Of note, we found that almost all these antiaging plant supplements increased the abundance of A. muciniphila to varying degrees [44][45][46][47]. However, it has not been possible to determine whether the anti-aging effects of these plant supplements are associated with an increased abundance of A. muciniphila.…”
Section: A Muciniphila and Agingmentioning
confidence: 80%